2012
DOI: 10.4137/ccrep.s8460
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis of Influenza Virus in an Elderly Hospitalized Patient: A Fatal Outcome

Abstract: Influenza is a well established cause of seasonal hospitalizations and deaths among older persons. However, influenza is frequently underdiagnosed by physicians, because its clinical presentations are often complex, particularly in elderly patients. We report the case of a 78-year-old woman admitted to the emergency department in January 2008 with fever, vomiting, and a history of asthenia and falls in the preceding three days. Diagnosis of influenza at admission was missed. Influenza was diagnosed by direct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Strategies for early PHU intervention should include education of ACF staff around interventions such as encouragement of annual influenza vaccinations as a preventive measure and consistently monitoring and identifying residents with influenza-like symptoms. This is especially important as research has indicated that elderly residents can have atypical presentations of influenza, therefore periodic testing for influenza even in the absence of fever may be warranted during the influenza season [23,24]. Active surveillance by PHU staff, such as phone calls to the ACFs during influenza season, is also an important strategy for the early identification of influenza outbreaks and could potentially lead to less morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for early PHU intervention should include education of ACF staff around interventions such as encouragement of annual influenza vaccinations as a preventive measure and consistently monitoring and identifying residents with influenza-like symptoms. This is especially important as research has indicated that elderly residents can have atypical presentations of influenza, therefore periodic testing for influenza even in the absence of fever may be warranted during the influenza season [23,24]. Active surveillance by PHU staff, such as phone calls to the ACFs during influenza season, is also an important strategy for the early identification of influenza outbreaks and could potentially lead to less morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The small sample size of ARI residents reduced the statistical power of any comparison by subgroups, especially for respiratory viruses other than influenza A(H3N2). Syndromic diagnosis of ARI is often complex in elderly patients as a consequence of preexisting diseases, complications, and atypical manifestation of ARIs, and it thus remains a challenge for physicians [34]. These difficulties could lead to biased clinical assessments and decisions regarding whether to take a swab, thus underestimating the number of positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…55 Although influenza has been principally classified as one of the predominant clinical complications of elderly patients with co-morbidities, it is often under-assessed and, its diagnosis could be challenging. 74,75 In addition to this, the patient's predominant cause of morbidity obscures the identification of essential symptoms and signs of influenza; furthermore, medical professionals tend to focus more on patients' known pathology. 74,[76][77][78][79] Outcomes in these patients aging 65 years or over, are usually fatal, some even do not develop pneumonia, and 89% die either because of pneumonia and influenza; pneumonia was equally responsible for high death reports during the Spanish flu of 1918.…”
Section: Polypharmacy and The Risk Of Infections In The Elderly Populmentioning
confidence: 99%
“…74,75 In addition to this, the patient's predominant cause of morbidity obscures the identification of essential symptoms and signs of influenza; furthermore, medical professionals tend to focus more on patients' known pathology. 74,[76][77][78][79] Outcomes in these patients aging 65 years or over, are usually fatal, some even do not develop pneumonia, and 89% die either because of pneumonia and influenza; pneumonia was equally responsible for high death reports during the Spanish flu of 1918. 80,81 Morbidity increases considerably among survivors, and up to 10-12% of these aged patient groups need a higher level of support for day to day work after discharge from hospital for acute respiratory diseases.…”
Section: Polypharmacy and The Risk Of Infections In The Elderly Populmentioning
confidence: 99%